Investigating the potential of carboxymethyl pullulan for protecting the rabbit eye from systematically induced precorneal tear film damage. (July 2019) - Singh, Ram Sarup; Kaur, Navpreet; Sharma, Radhika; Rana, Vikas
Abstract: The present investigation was aimed to develop a rabbit model for protecting the rabbit eye from systematically induced precorneal tear film (PTF) damage, evaluation of carboxymethyl pullulan for its protective action against PTF damage and its curative potential. For the same, pullulan was modified by carboxymethylation and structural modification was confirmed by spectral attributes. Further, the carboxymethyl pullulan (CMP) solutions (0.1–2.0%, w/v) were evaluated for their physical properties and its concentration 1.5% (w/v) was found to fit the criterion to prepare an eye solution. The safety and non-toxicity of CMP (1.5%, w/v) eye solution was confirmed by HET-CAM method and rabbit eye irritation test. Further, a systematic rabbit eye model was developed that mimic PTF damage in day to day life. Therefore, three levels of PTF damage were developed equating symptoms of damage due to high temperature (level I) or long term mobile use (level II) or heavy air pollution (level III). Thus, a representative model with benzalkonium chloride (BAC, 0.1% v/v, 0.2% v/v and 0.3% v/v), administered two drops twice a day for two days to develop level I, level II and level III eye damage. The CMP (1.5%, w/v) eye solution possessed a protective potential against level I and II PTF damage. The rabbit eyes remained unharmed and comparable with the normal control during the complete experimental period. Additionally, CMP (1.5%, w/v) eye solution has shown early fast recovery (8 days) from PTF damage induced by instillation of PTF damage agent (BAC). Carboxymethyl pullulan eye protective solution has normalized the tear film stability in rabbit eye model. It is established from the present work that, carboxymethyl pullulan has protective action against precorneal tear film damage and it potentiates the early recovery too. Highlights: Rabbit model for systematically induced precorneal tear film damage was developed. CMP protects eyes from damage by weather level I or long term mobile use level II. CMP showed early complete recovery from PTF damage.